Magnetic Resonance Imaging Confirmed Olfactory Bulb Reduction in Long COVID-19: Literature Review and Case Series - Andrea Frosolini; Daniela Parrino; Cristoforo Fabbris; Francesco Fantin; Ingrid Inches; Sara Invitto; Giacomo Spinato; Cosimo De Filippis (Brain Sciences, 2022)
An altered sense of smell and taste was recognized as one of the most characteristic symptoms of coronavirus infection disease (COVID-19). Despite most patients experiencing a complete functional resolution, there is a 21.3% prevalence of persistent alteration at 12 months after infection. To date, magnetic resonance imaging (MRI) findings in these patients have been variable and not clearly defined. We aimed to clarify radiological alterations of olfactory pathways in patients with long COVID-19 characterized by olfactory dysfunction. A comprehensive review of the English literature was performed by analyzing relevant papers about this topic. A case series was presented: all patients underwent complete otorhinolaryngology evaluation including the Sniffin’ Sticks battery test. A previous diagnosis of SARS-CoV-2 infection was confirmed by positive swabs. The MRIs were acquired using a 3.0T MR scanner with a standardized protocol for olfactory tract analysis. Images were first analysed by a dedicated neuroradiologist and subsequently reviewed and compared with the previous available MRIs. The review of the literature retrieved 25 studies; most cases of olfactory dysfunction more than 3 months after SARS-CoV-2 infection showed olfactory bulb (OB) reduction. Patients in the personal case series had asymmetry and a reduction in the volume of the OB. This evidence was strengthened by the comparison with a previous MRI, where the OBs were normal. The results preliminarily confirmed OB reduction in cases of long COVID-19 with an altered sense of smell. Further studies are needed to clarify the epidemiology, pathophysiology and prognosis.